Fin control for ship roll motion stabilisation based on observer enhanced MPC with disturbance rate compensation. (15th March 2021) - Jimoh, Isah Abdulrasheed; Küçükdemiral, Ibrahim Beklan; Bevan, Geraint
Abstract: In this paper, a disturbance observer enhanced model predictive controller (MPC) which compensates for the wave-induced disturbance magnitude and rate is proposed for the ship roll motion stabilisation problem. The velocity model of the ship roll motion is used in the controller design to handle slowly varying modelling uncertainties and external disturbances. The rate of change of the disturbances induced by waves is then attenuated by formulating a control input that incorporates the estimated disturbance rate such that it is always in opposition to the rate of the environmental disturbances. The disturbance estimation was achieved by designing an observer based on convex optimisation formulated as an H 2 minimisation problem. Numerical simulation studies, under various conditions of the sea, showed the effectiveness of the proposed MPC scheme in reducing the undesired ship roll motion induced by sea waves. Highlights: An optimal estimator is designed for the estimation of uncertain wave-induced disturbances causing unwanted ship roll motion. The modelling errors and magnitude of the wave-induced disturbances are rejected by using a velocity model of the vessel. The estimated disturbance rate is used to attenuate the rate-of-change of the actual wave-induced disturbances. Realistic magnitude and rate constraints on the fin actuator are considered in the proposed predictive controller.